Outsourcing w działalności bankowej – wybrane zagadnienia - Sagan, Marta (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2018)
Main point of the article is the characteristics of selected issues related to outsourcing in banking activities. The study begins with an explanation of the concept of outsourcing, taking into account the specifics of banking outsourcing and providing the legal basis and genesis of this institution in Polish banking law. Next, the issue of the outsourcing agreement is discussed as an agency agreement. The mode of entrusting data by the bank to an external entity is described and the problems of outsourcing regulations in relation to banking secrecy regulations are also taken into account. In this study, a formal-dogmatic method was used
Keywords: outsourcing; banking activities; banking secrecy